2021
DOI: 10.1021/acscatal.0c04735
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Generation with 100% Faradaic Efficiency on Metal-Free Carbon Black

Abstract: Electrochemical oxygen reduction to hydrogen peroxide is now being studied as a promising renewable and localized alternative for the traditional complex anthraquinone process. Catalysts for this two-electron reduction pathway with high selectivity are required to achieve industrialization. Here, we disclose an inexpensive metal-free catalyst that is synthesized from commercial carbon black (CB) with a one-step plasma method for the affordable electrochemical generation of hydrogen peroxide in 100% Faradaic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 59 publications
1
101
0
1
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31][32][33][34][35] Wherein, the oxygen-doped carbon catalysts have gained the special attentions because of their high H 2 O 2 selectivity during ORR. [36][37][38][39][40][41][42] For example,D ong et al [42] reported that the superhydrophilic honeycomb carbon nanofiber with rich oxygenated functional groups showed high H 2 O 2 selectivity during ORR. In this community,r esearchers focus on developing highly efficient catalyst and identifying the active sites for 2e À ORR.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35] Wherein, the oxygen-doped carbon catalysts have gained the special attentions because of their high H 2 O 2 selectivity during ORR. [36][37][38][39][40][41][42] For example,D ong et al [42] reported that the superhydrophilic honeycomb carbon nanofiber with rich oxygenated functional groups showed high H 2 O 2 selectivity during ORR. In this community,r esearchers focus on developing highly efficient catalyst and identifying the active sites for 2e À ORR.…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, SW defect is further depicted in Figure 4d1, which is reconstructed from four hexagonal carbon rings. Moreover, theoretical and experimental studies suggest that the carbon atoms simultaneously linked by 5-7 rings in SW defects are active sites to facilitate the ORHP 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Chiefly, oxidized carbon materials (such as oxidized carbon black 7 , oxidized CNTs 8 , oxygenated graphitic nanoplatelets 9 ) have emerged as a type of promising catalyst for ORHP, due to the oxygen moieties improving the OOH* absorption capacity of the adjacent carbon atoms. Nevertheless, oxidized carbon materials generally suffer from surface oxidization at high current, showing sluggish kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] However, recent work indicated that the carbon defects generated during the oxidation process also play an important role. [ 71 ] Effects may be more complicated in N‐doped and other heteroatom‐doped materials. Further exploration can help understand the catalytic process and design better catalysts.…”
Section: Discussionmentioning
confidence: 99%